Evolution of heavy metals during thermal treatment of manure: A critical review and outlooks. (May 2020) - Li, Shuhui; Zou, Dongsheng; Li, Longcheng; Wu, Ling; Liu, Fen; Zeng, Xinyi; Wang, Hua; Zhu, Yufeng; Xiao, Zhihua
Abstract: Manure treatment has become a focal issue in relation to current national policies on environmental and renewable energy matters. Heavy metals can be excreted with the animal manure, contributing to pollution of soil and water. Therefore, animal manure needs proper treatment before application to agricultural soils. Here, we review the species transformation of HMs and fate during incineration, pyrolysis, gasification and hydrothermal processing of animal manures. During thermal processes, 75%–90% of thermally stable HMs such as Cr, Ni, and Mn were concentrated in the solid-phase. HMs with less thermal stability such as Cd, As, Hg, and Pb are inclined to concentrate in the aqueous phase and gas phase, accounting for less than 5% of their total concentrations. In general, thermal processes transform HMs in the exchangeable fraction with high biotoxicity to oxidizable fraction or residual fraction with less bioavailability. In addition, the operating conditions and co-processing with other materials may influence the species transformation of HMs. Finally, recommendations for future research on the proper disposal and utilization of animal manure are proposed. More large-scale experiments are required to elucidate the precise mechanism behind the immobilization of HMs. The influence of additives (catalysts and HM stabilizers) and the influence of the type of solvent on HM transformation needs further study. Highlights: Outline the current methods of thermal treatments for animal manure. Fate of heavy metals during the thermal treatments of animal manure. Fractions of unstable metals in manures were immobilized during thermal treatments. Few researches had based on large-scale experiments and risk evaluation of HMs.